Multilevel Analysis of Academic Factors Influencing Academic Outcomes in Mathematics - Arvin M. Larobis; Marlon S. Frias (Future Science / FSH-PH Publications, 2026)
Mathematics skill is a significant indicator of a school’s quality as well as a nation’s competitive edge globally. Despite its significance, academic achievement gaps among nations and school settings remain prominent. The current study investigated how institutional and teacher-related factors predict mathematics proficiency among secondary students in junior high schools in Region XI, Philippines. A quantitative multilevel approach was employed to analyse data from 114 licensed junior high school mathematics teachers across 30 public and private junior high schools in five city divisions of the region. A 70-item researcher-developed instrument was used to assess institutional factors (professional development engagement, supportive school administration, and availability and use of school resources) and teacher-related factors (pedagogical content knowledge, mathematics teaching self-efficacy, teaching practices, and students’ classroom engagement). Students’ mathematics proficiency was measured using their quarterly grades from the end of the second academic year. This study applies hierarchical linear models (HLM) to examine student, teacher, and school-level predictors of mathematics proficiency. Findings reveal that both pedagogical content knowledge and teacher self-efficacy are strong predictors of student achievement. Moreover, findings suggest that teacher practices and student engagement are significant predictors of mathematics proficiency. At the institutional level, findings show that supportive school leadership and professional development engagement are significant predictors of teacher practices and mathematics student proficiency.